In vitro Effects of 0.05% Cetylpyridinium Chloride and 1% Povidone Iodine on Flexural Strength of Nickel-Titanium Orthodontic Wires - Mohammadian , Manijeh; Ghiasi , Parisa; Soleimani, Milad (Galen Medical Journal, 2025)
Background: This study assessed the effects of 0.05% cetylpyridinium chloride (CPC) and 1% povidone iodine (PI) on flexural strength of nickel-titanium (NiTi) orthodontic wires. Materials and Methods: In this in vitro, experimental study, 27 pieces of NiTi orthodontic wires were randomly assigned to three groups (n=9) for immersion in 0.05% CPC, 1% PI, and distilled water (control) at 37°C for 90 minutes. After immersion, the modulus of elasticity, the yield strength, the mean force during the loading and unloading phases at 0.5 mm intervals of each wire (0.5, 1, 2.5, 2, and 2.5 mm), and the flexural strength of the wires were measured by the three-point bending test. Surface topography and corrosion of the wires were also inspected under a scanning electron microscope (SEM). Data were analyzed by one-way ANOVA and Tukey test (alpha=0.05). Results: CPC significantly increased the flexural strength of the wires (P<0.05); while, the flexural strength was not significantly different in the PI and control groups (P>0.05). CPC significantly increased the generated force during loading at all bending points and during unloading at 0.5- and 1-mm points (P<0.05). PI increased the generated force during loading at 0.5 and 1 mm, and during unloading at 2.5 mm point (P<0.05). CPC and PI had no significant effect on the yield strength in loading and unloading phases (P>0.05). CPC and PI caused superficial corrosion of the wires. Conclusion: CPC (0.05%) and PI (1%) increased the mean force generated during unloading of the wires, their modulus of elasticity, and flexural strength.